THE IMPACT OF SINGAPORE COASTAL RECLAMATION AGAINST MARITIME BOUNDARIES AND TERRITORIAL SOVEREIGNTY OF INDONESIA-SINGAPORE - Arni Nur Sukma Pertiwi; Hardi Alunaza SD; Adityo Darmawan Sudagung (Jurnal Asia Pacific Studies, 2018)
Singapore has undertaken coastal reclamation activities since 1976 in the southwest of Singapore's main island bordering the Nipa Island, Riau Archipelago, Indonesia. In reclamation, Singapore took sand from Nipa Island Indonesia bounded by the sea with Singapore. This reclamation will have an impact on several things that is the maritime boundaries and the territorial sovereignty of both countries. This article is attempted to describe how the impact of Singapore coastal reclamation against the maritime boundary and territorial sovereignty of Indonesia-Singapore. The author is using the concept of State Sovereigntyand the International Maritime Law in UNCLOS 1982. Furthermore, this paper is using the descriptive method with the qualitative approach. The data collection technique is literature study consisting of books, journals, and including data from the reliable website in supporting the explanation of this paper. Based on the provisions of UNCLOS 1982, it can be concluded that Singapore's coastal reclamation has no effect on the maritime boundary between Indonesia and Singapore, where maritime boundaries remain at baseline before Singapore reclamates. However, Singapore's coastal reclamation could threaten Indonesia's territorial sovereignty as the mainland of Singapore approaching Nipa Island Indonesia can assume that Singapore wants to take control of Nipa Island, especially the Nipa Island region is strategically located because of its near to the Singapore Strait which is an international shipping line.